PENGARUH KUALITAS PELAPORAN KEUANGAN, LEVERAGEKEUANGAN, DAN UKURAN PERUSAHAAN TERHADAPHARGA SAHAM PERUSAHAAN: Studi pada Perusahaan Manufaktur Sub Sektor Kosmetik dan Barang Keperluan Rumah Tangga yang Terdaftar di Bursa Efek Indonesia Periode Tahun 2017-2019 (Prospect : Jurnal Manajemen dan Akuntansi, 2021)
This study aims to examine the effect of Financial Reporting Quality, Financial Leverage, and Company Size on Company Stock Prices (Study on Manufacturing Companies in the Cosmetics and Household Goods Sub-Sector Listed on the Indonesia Stock Exchange for the 2017-2019 Period). The population in this study is the Manufacturing Sub-Sector of Cosmetics and Household Goods listed on the Indonesia Stock Exchange (IDX) in 2017-2019 as many as 6 companies. The sampling method used is purposive sampling, where the sample that meets the criteria is 5 companies over a period of 3 years, then the number of samples of research data is 15. The analysis technique used is calculating each variable, descriptive statistical test, classical assumption test, statistical analysis test, and hypothesis testing. The results of this study indicate that the quality of financial reporting, financial leverage, and company size affect the company's stock price.